LANDSCAPE CHANGES BASED ON HYDROLOGICAL CHARACTERISTICS IN THE WAE RIUAPA WATERSHED WEST SERAM REGENCY, MALUKU, INDONESIA - Patimang, Anthoinete Linda; Papilaya, Patrich Ph. E.; Latuamury, Bokiraiya (MAKILA, 2024)
Changes in the Wae Riuapa River Basin landscape in West Seram Regency, Maluku, reflect complex ecological and social dynamics. The Wae Riuapa watershed is an integral part of the hydrological cycle in the region, influencing water availability, water quality, and geomorphological processes. This research aims to model changes in the landscape of the Wae Riuappa watershed regarding hydrological characteristics. The research method uses ArcGIS 10.3 for spatial analysis of 2010 and 2020 Landsat images and hydrooffice 12.0 software, BFLOW 3.0 module, a hydrological model for graphical separation of daily discharge. The results of modeling landscape changes in the Wae Riuappa watershed on hydrological characteristics obtained a regression model that depicts landscape changes as having a significant simultaneous and partial influence on discharge conditions in the Wae Riuappa watershed during the research period. The spatial pattern of area distribution for the nine land cover types in the study period was relatively similar. Widespread forest land cover still dominates the landscape of the Wae Riuapa watershed. However, the pattern of widespread distribution of changes is starting to decrease in primary and secondary forest land cover. Meanwhile, the distribution pattern of changes in agricultural land and mixed gardens and settlements has increased slowly and significantly. The results of a multi-temporal analysis of the hydrological characteristics of the Wae Riuapa watershed show that the daily discharge trend experiences multi-temporal fluctuations.